2004
DOI: 10.17221/10640-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence spectroscopy for monitoring extra virgin olive oil deterioration upon heating

Abstract: Fluorescence spectroscopy is a reliable and fast method for determining the deterioration of extra virgin olive oil (EVOO). EVOO was analysed by HPLC for determining antioxidant changes in EVOO due to heating at 170°C for 3 h. This thermal oxidation caused a significant exponential decrease in hydroxytyrosol (OH-Tyr) and vitamin E (vitE), while the reduction in the tyrosol content was relatively small. Hydroperoxydes were analysed by an indirect colorimetric method. Their content decreased exponentially during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Fluorescence spectrometry and PLSR can be used as a rapid technique for evaluating the quality of heat-treated extra virgin olive (Cheikhousman et al 2004) and rapeseed oils (Mas et al 2004).…”
Section: Edible Oilsmentioning
confidence: 99%
“…Fluorescence spectrometry and PLSR can be used as a rapid technique for evaluating the quality of heat-treated extra virgin olive (Cheikhousman et al 2004) and rapeseed oils (Mas et al 2004).…”
Section: Edible Oilsmentioning
confidence: 99%
“…The negative peak at 288 nm should correspond to polyphenols. [18,46] Moreover, it is also worthy to note that the dispersion of capped and uncapped LO samples in their group (cluster) appears to follow a tendency in accordance with the evolution of the storage time. No difference was noticed between capped and uncapped samples.…”
Section: Fluorescence Properties Of Spectra Acquired On Oil Samples Throughout Storage After Excitation Set At 250-310 Nm and Emission Sementioning
confidence: 80%
“…Although the excitation fluorescence spectra of RO and SO did not provide a maximum fluorescence intensity at this wavelength, they exhibited a shoulder corresponding to the development of new fluorescent components related to the degradation of hydroperoxides products. [ 46 ] Indeed, aldehydes and polymers of certain components, which fluoresce at this wavelength of excitation, could derive from hydroperoxide. From these observations, it can be concluded that the shape of these fluorescence excitation spectra could be considered as fingerprints allowing the differentiation between the four oil types.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As most of these bioactive compounds (including phenolic compounds) are gradually lost there are no differences in behavior between the different grades of olive oil. In addition, the polyphenols content is affected by the thermal process, but their loss depends on their molecular structure (Gómez-Alonso et al, 2003;Carrasco-Pancorbo et al, 2007;Cheikhousman et al, 2005;Daskalaki et al, 2009;Romero et al, 2003).…”
Section: Introductionmentioning
confidence: 99%